The Rewards of Selfish Mining. - Goldberg, Sharon; Heilman, Ethan (Communications of the ACM, 2018)
The article presents an introduction to a paper by Eyal and Sirer which questions the assumption that all Bitcoin miners have the same view of the blockchain and will immediately announce their solutions to computational puzzles to the network.